Efek ekstrak etanol kedelai hitam (Glycine soja) terhadap ketebalan dermis mencit (Mus musculus L.) pasca unilateral ovariektomi - Akyun, Isna Kurotul; Fajariyah, Susantin; Mahriani, Mahriani (Jurnal Biologi Udayana; Vol 23 No 2 (2019): JURNAL BIOLOGI UDAYANA, 2019)
Estrogen is a steroid hormone produced by the ovaries. Estrogen is a hormone that triggers collagen synthesis by fibroblast.Collagen has affects for thickness of dermis.Estrogen deficiency can lead disruption collagen synthesis, so has an impact on decline dermis thickness. Unilateral ovariectomy is the act of removal of one ovary in the female reproductive system and is a model for estrogen deficiency. The condition of estrogen deficiency can be overcome by giving phytoestrogens. Black soybean seed is one of phytoestrogens source. The purpose of this study was to determine the effect of black soybean extract after ovariectomy on increasing on dermis thickness (Mus musculus L.). The dosage of black soybean ethanol extract used was 0.31 g / ml / day and 0.63 g / ml / day administered orally (gavage) for 20 days. The results showed a dose of 0.31 g / ml / day may and 0.63 g / ml / day increase dermis thickness of mice.